GH Responsiveness in Children With Noonan Syndrome Compared to Turner Syndrome - Dahlgren, Jovanna; Albertsson-Wikland, Kerstin (Frontiers in Endocrinology, 2021)
Background: Despite different genetic background, Noonan syndrome (NS) shares similar phenotype features to Turner syndrome (TS) such as short stature, webbed neck and congenital heart defects. TS is an entity with decreased growth hormone (GH) responsiveness. Whether this is found in NS is debated. Methods: Data was retrieved from combined intervention studies including 25 children diagnosed with NS, 40 diagnosed with TS, and 45 control children (all prepubertal). NS-children and TS-girls were rhGH treated after investigation of the GH/IGFI-axis. GH was measured with poly- and monoclonal antibodies; 24hGH-profile pattern analysed by PULSAR. The NS-children were randomly assigned to Norditropin® 33 or 66 μg/kg/day, and TS-girls were consecutively treated with Genotropin® 33 or 66 μg/kg/day. Results: Higher PULSAR-estimates of 24h-profiles were found in both NS-children and TS-girls compared to controls: Polyclonal GHmax24h-profile (Mean±SD) was higher in both groups (44±23mU/L, p<0.01 in NS; 51±47, p<0.001 in TS; compared to 30±23 mU/L in controls) as was GH-baseline (1.4±0.6 mU/L in NS; 2.4±2.4 mU/L in TS, p<0.01 for both, compared to 1.1±1.2 mU/L in controls). Pre-treatment IGFISDS was 2.2 lower in NS-children (-1.7±1.3) compared to TS-girls (0.6±1.8, p<0.0001). GHmax, IGFI/IGFBP3-ratioSDS, and chronological age at start of GH accounted for 59% of the variance in first-year growth response in NS. Conclusion: Both prepubertal NS-children and TS-girls had a high GH secretion, but low IGFI/IGFBP3 levels only in NS-children. Both groups presented a broad individual response. NS-children showed higher response in IGFI and growth to less degree, pointing to higher responsiveness to GH treatment than TS-girls.